Application analysis of MBTI occupational personality types in classroom group project teaching - Zongyi Zhang (SHS Web of Conferences)
In this paper, the project teaching reform is carried out in the course of “Production Logistics”, and it is found that in the project teaching activities, the personality composition of the group members has a great impact on the effect and achievement of the project activities. Therefore, this paper uses MyersBriggs Type Indicator(For short MBTl ) professional personality test to investigate the students, obtain the overall distribution of the vocational personality types of the students, and compare the achievement differences of different professional personalities. Analyze the influence of different professional personalities of team members on the achievement of project-based courses. By analyzing theinfluence of different professional personalities of group members on project-based courseactivities, the following conclusions are drawn: lNFP is the most common type of studentpersonality type, ESFl is the least. lNFl and ENFl students have better grades, ET type students havea stronger willingness to be group leaders, while EF type students have a better willingness to begroup leaders; in terms of the composition of group members, the more complex the type, whenthe proportion of certain personality type is about50%, the group performance isrelatively bette.